The bone orchard - Doiron, Paul (New York : Minotaur Books, 2014)
In the aftermath of a family tragedy, Mike Bowditch has left the Maine Warden Service and is working as a fishing guide in the North Woods. But when his mentor Sgt. Kathy Frost is forced to kill a troubled war veteran in an apparent case of "suicide by cop," he begins having second thoughts about his decision.
Maine author.
Keywords: Game wardens -- Fiction; Wilderness areas -- Maine -- Fiction; Veterans -- Fiction; Maine -- Fiction; Suspense fiction; Mystery fiction